Expressão gênica associada ao conteúdo de minerais no músculo Longissimus thoracis e seus processos regulatórios em bovinos Nelore (Bos indicus) - Afonso, Juliana (2019)
The mineral concentration of the bovine muscle does not only depend on the balance between the ingestion and excretion of minerals, but also the environment, breed and genetic factors. In addition, mineral content can affect biological processes related to meat quality, acting in chemical reactions related to tenderness in postmortem as well as in the maintanance of muscular cells throught its action in methabolism, as enzimatic co-factors and in the regulation of cell replication and differentiation. Since detecting genetic elements involved with mineral homeostasis is of interest to the meat industry, we present analyzes performed for this purpose. Differential gene expression tests were performed in muscle Longissiumus thoracis of groups of Nelore steers contrasting separately to the concentration of the minerals calcium, copper, potassium, magnesium, sodium, phosphorus, sulfur, selenium and zinc. The iron mineral was not included in these analyses because the differentially expressed genes related to iron concentration in the same population in study were already published by our research group. A functional enrichment of the differentially expressed genes was made, also verifying protein-protein interactions known among them, in search of biological processes related to each mineral. Then, also including iron concentration data, two new approaches were developed to use the PCIT (Partial Correlation Coefficient with Information Theory) and RIF algorithms (Regulatory Impact Factor). The new applications for using these algorithms allowed the direct identification of genetic elements correlated to the mineral concentration continuously in our population and the quantification of the regulatory impact of the genes and miRNAs correlated to a mineral on the concentration of this mineral. The regulation of the pathways related to adipogenesis was significant and the genes indicated here may explain the antagonistic effect known between Cu and Zn in the biosynthesis of fatty acids. With the new applications to use the PCIT and RIF algorithms, genes known to be linked to mineral homeostasis with high regulatory impact were identified and previously indicated as regulatory in our population for being transcription factors, eQTLs or miRNAs. The PLCB2 gene is correlated with Fe and S, the latter correlates to the other minerals. The NOX1 gene possessed significant RIF and is correlated to Se. In humans, the concentration of zinc regulates NOX1. We conclude that the core of genetic regulation for all minerals studied seems to be in the interactions between the components of the extracellular matrix. We can infer that the integration of the proposed techniques in our work may include a new level of information about the regulatory elements involved in mineral homeostasis.